2022
DOI: 10.1177/15353702221104033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cell injury induced by inhaled molybdenum trioxide nanoparticles in Golden Syrian Hamsters

Abstract: Molybdenum trioxide nanoparticles (MoO3 NPs) are extensively used in the biomedical, agricultural, and engineering fields that may increase exposure and adverse health effects to the human population. The purpose of this study is to evaluate a possible molecular mechanism leading to cell damage and death following pulmonary exposure to inhaled MoO3 NPs. Animals were separated into four groups: two control groups exposed to room air or aerosolized water and two treated groups exposed to aerosolized MoO3 NPs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…The initial histopathological lung damages were observed already at 10 mg/m 3 . In another study, Huber and Cerreta [ 37 ] reported an increase in the neutrophils and multinucleated macrophages in BAL fluid in hamsters after one day of inhalation of 5 mg Mo/m 3 , and lymphocytes after 7 days of exposure. The increase in neutrophils in BAL fluid was also observed in mice after inhalation of 90 mg Mo/m 3 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial histopathological lung damages were observed already at 10 mg/m 3 . In another study, Huber and Cerreta [ 37 ] reported an increase in the neutrophils and multinucleated macrophages in BAL fluid in hamsters after one day of inhalation of 5 mg Mo/m 3 , and lymphocytes after 7 days of exposure. The increase in neutrophils in BAL fluid was also observed in mice after inhalation of 90 mg Mo/m 3 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this thematic issue, there are six mini-reviews and two original research articles targeting, toxicology, 1 pathogen and exosome detection, 2,3 spinal cord injury, 4 tissue scaffolds, 5 molecular barcoding, 6 RNA biology, 7 and bio-hybrid electronic devices 8 that bridge biology with nanotechnology and the bionanoscience interface.…”
mentioning
confidence: 99%
“…In the area of nanotoxicology, Huber and Cerreta 1 demonstrate how inhaled nanoparticles exert their toxicological effect using a well-established model for lung diseases, Golden Syrian Hamsters. Exposure to molybdenum oxide nanoparticles that are commonly used as additives in a variety of industrial applications damages the lung by interfering with autophagy, activating inflammasome leading to lung inflammation, damage, and toxicity.…”
mentioning
confidence: 99%